Defining the Need for Genetic Stock Assignment when Describing Stock Demographics and Dynamics: an Example using Lake Whitefish in Lake Michigan. Issue 4 (27th May 2020) - Isermann, Daniel A.; Belnap, Matthew J.; Turnquist, Keith N.; Sloss, Brian L.; VanDeHey, Justin A.; Hansen, Scott P.; Caroffino, David C.
Abstract: Genetic stock assignment is not routinely used when describing the dynamics and demographics of individual stocks supporting mixed‐stock fisheries, and capture location and timing are often used as alternative assignment methods. However, variation in stock demographics and dynamics may not be accounted for if stock assignments based on capture location or timing do not accurately reflect genetic assignments. We used Lake Whitefish Coregonus clupeaformis in Lake Michigan as a model fishery to determine whether stock mixing could undermine efforts to describe stock status when using October capture location as a proxy for genetic stock assignment. Accuracy of stock assignments based on October capture location ranged from 54% to 100% among management zones. Metrics describing length and age distributions, weight at length, fecundity, and growth varied among genetic stocks. Stock‐specific metrics were typically similar between stock assignment methods (capture location versus genetics) because only one or two genetic stocks were collected in most locations and the majority of those fish were from spatially proximal stocks with similar metrics. However, more extensive mixing of Lake Whitefish stocks has been documented; thus, using capture location for stock assignment could result in incorrect conclusions regarding stock status and harvest management depending on stock composition. Ambiguity in genetic stock assignments was a problem in two management zones, where between 23% and 42% of Lake Whitefish did not assign to a specific stock with a probability of at least 0.70. In the future, using genomic techniques rather than microsatellites may provide different conclusions regarding genetic stock structure; these differences could affect the accuracy of using capture location for stock assignment. Use of capture location as a proxy for genetic stock assignment may not be warranted for all mixed‐stock fisheries but may be appropriate when stock mixing is limited or is restricted to stocks with consistently similar characteristics.